Impacto da posição prona em pacientes com diabetes tipo 2 e Covid-19 em ventilação mecânica invasiva - Rossato, Claudia Turra (2024)
Introduction: Patients with type 2 diabetes mellitus (T2D) were widerly affected by the pandemic resulting from the Coronavirus 2019 (COVID-19). Covid-19 studies involving intubated patients focused on assessing oxygenation status, ventilatory mechanics, intensive care unit (ICU) and/or hospital stay and mortality in response to prone position in several populations. However, the impact of prone position remains uncertain in critically ill patients with T2D and COVID-19. Objective: To evaluate the impact of prone position in patients with T2D and COVID-19 during ICU admission. Methods: This is a retrospective, multicenter cohort study conduced in five brasilian hospitals. The sample consisted of patients with T2D a confirmed or highly suspected diagnosis of COVID-19, who progressed to severe acute respiratory distress syndrome (ARDS). The patients were compared between pronated and non-pronated patients, as well as between responders (increased in PaO2/FiO2 ratio > 20mmHg after the first prone session) and non-responders to prone positioning. The following outcomes were recorded: in-hospital mortality, reintubation and tracheostomy rates, durations of invasive mechanical ventilation (IMV), length of ICU and hospital stay, oxygenation based on the PaO2/FiO2 ratio, ventilatory response based on mechanical ventilation parameters. The prone positioning maneuver was performed by trained teams and followed the protocols of each inpatient unit, with parameters defined by consensus among the participating centers. Results: A total of 296 patientes (194 prone and 102 non-prone) with similar baseline characteristics werw studied. The mortality rate in prone patients was lower than in-non-prone patients [44.3% vs. 61.7%; RR 0.72 (95% CI: 0.58 to 0.89)] and a number needed to treat (NNT) of 5.74 (95% CI 3.4 to 17.6) was obtained. The incidence of reintubation and tracheostomy did not differ between groups. The duration of IMV and ICU and hospital stays recorded in survivors was similar between groups. Most patients were prone responders (79.9%) and had a lower mortality rate than non-responders [40% vs. 59%; RR 0.68 (95% CI: 0.49 to 0.94)] and a lower risk of related complications [2.6% vs. 15.4%; RR 0.17 (95% CI: 0.05 to 0.57)]. After the first prone positioning session, surviving patients showed a better response in the PaO2/FiO2 ratio compared to nonsurvivors (mean difference: 49.9 mmHg; 95% CI: 34.2 to 65.7). Conclusion: The prone position reduced the risk of mortality during hospitalization in patients with T2DM and severe ARDS associated with COVID-19. One death can be prevented for every 6 patients treated. Responders to the prone positioning also demonstrated a lower mortality rate and a lower risk of prone-related complications. The improvement in oxygenation after the first prone positioning session may be related to the greater survival of prone patients.